Perlindungan Hak Terhadap Narapidana Perempuan Menyusui di Lembaga Pemasyarakatan (Studi Kasus Lembaga Pemasyarakatan Perempuan Kelas IIA Tangerang) - Guntara, Bima; Kusumawardhani, Suci (Program Studi Hukum Universitas Pamulang, 2024)
Correctional institutions as government bodies under the auspices of the Directorate General of Corrections, Ministry of Law and Human Rights, are places for training prisoners and correctional students in Indonesia. Prisons that exist today are not the same as prisons that existed in the past. The current prison is the result of the implementation of the correctional system (treatment system for prisoners). In this system, perpetrators of criminal acts are put into institutions not as a form of state revenge for the criminal acts they have committed, but as a place for convict training (treatment of violators). In prison, correctional inmates will not receive various forms of torture and physical suffering, but rather efforts aimed at making the perpetrators of the crime concerned aware of their mistakes. Female prisoners are citizens who must be protected and given their natural rights, including menstruation, pregnancy, childbirth and breastfeeding. This characteristic is the main basis for the need for legal protection for female prisoners. In this case, so-called female prisoners or female prisoners in correctional institutions have different needs than men, for example a woman will experience a menstrual cycle so the issue of hygiene becomes something that needs more attention. Apart from that, female inmates who are pregnant or about to give birth also need special care to ensure the health of the mother and child. When the child is born, the woman can also breastfeed.